If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(p-3)+5=2(p+1)-1
We move all terms to the left:
4(p-3)+5-(2(p+1)-1)=0
We multiply parentheses
4p-(2(p+1)-1)-12+5=0
We calculate terms in parentheses: -(2(p+1)-1), so:We add all the numbers together, and all the variables
2(p+1)-1
We multiply parentheses
2p+2-1
We add all the numbers together, and all the variables
2p+1
Back to the equation:
-(2p+1)
4p-(2p+1)-7=0
We get rid of parentheses
4p-2p-1-7=0
We add all the numbers together, and all the variables
2p-8=0
We move all terms containing p to the left, all other terms to the right
2p=8
p=8/2
p=4
| |x-68|=3.5 | | 54-9x+x^2=0 | | 1/4=0,25x | | 3x-61=17 | | 3(2x+1)x=−8 | | 0.7=0.101x+0.044 | | 5x-18=3x+18 | | (2)(3^x)=(7^2x-5) | | A=3n-8 | | t^2+6t-72=0 | | 5y+14=21 | | 4x+1-2x=7 | | x^2+2x-0.64=0 | | 86=2n-(4-3n) | | 8.3333÷x=2.33333÷9.1 | | 2x-400=1,200 | | k−(−65)=−6/1 | | k−(−65 )=−6/1 | | k−(−65 )=−6/1 | | 5-(4x-6)=3x-10 | | -4+9x=-49 | | -w+206=118 | | y-4=2y-14 | | 2x+45=3x+20 | | 5x-15=2x=21 | | 12+3x=7x-4 | | 6-6m+6-4=2 | | 5(n+2)=-17-4n | | 2b-3=0.3 | | 5.6x+900=31.36+30x | | 4x+30=8x-6 | | 1/3(6/7-2x)-3/7=6/7 |